Fusobacterium nucleatum secretes amyloid‐like FadA to enhance pathogenicity. (29th June 2021) - Meng, Qing; Gao, Qiuqiang; Mehrazarin, Shebli; Tangwanichgapong, Kamonchanok; Wang, Yu; Huang, Yiming; Pan, Yutong; Robinson, Samuel; Liu, Ziwen; Zangiabadi, Amirali; Lux, Renate; Papapanou, Panos N; et al.
Abstract: Fusobacterium nucleatum ( Fn ) is a Gram‐negative oral commensal, prevalent in various human diseases. It is unknown how this common commensal converts to a rampant pathogen. We report that Fn secretes an adhesin (FadA) with amyloid properties via a Fap2‐like autotransporter to enhance its virulence. The extracellular FadA binds Congo Red, Thioflavin‐T, and antibodies raised against human amyloid β42. Fn produces amyloid‐like FadA under stress and disease conditions, but not in healthy sites or tissues. It functions as a scaffold for biofilm formation, confers acid tolerance, and mediates Fn binding to host cells. Furthermore, amyloid‐like FadA induces periodontal bone loss and promotes CRC progression in mice, with virulence attenuated by amyloid‐binding compounds. The uncleaved signal peptide of FadA is required for the formation and stability of mature amyloid FadA fibrils. We propose a model in which hydrophobic signal peptides serve as "hooks" to crosslink neighboring FadA filaments to form a stable amyloid‐like structure. Our study provides a potential mechanistic link between periodontal disease and CRC and suggests anti‐amyloid therapies as possible interventions for Fn ‐mediated disease processes. Synopsis: Fusobacterium nucleatum, an oral commensal anaerobe, secretes amyloid‐like FadA to enhance its pathogenicity. Intact pre‐FadA is a critical component of amyloid‐like FadA, which is secreted via the autotransporter Fap2. Fusobacterium nucleatum (Fn) secretes amyloid‐like FadA, promoting periodontal bone loss and colorectal cancer. Amyloid‐binding compounds disrupt Fn pathogenicity in a FadA‐dependent manner. Amyloid‐like FadA facilitates Fn biofilm formation, acid tolerance and binding to host cells. Abstract : Fusobacterium nucleatum, an oral commensal anaerobe, secretes amyloid‐like FadA to enhance its pathogenicity. Intact pre‐FadA is a critical component of amyloid‐like FadA, which is secreted via the autotransporter Fap2.